3D physical modeling for checking Level III probabilistic design in breakwaters: A case study in Punta Langosteira Port, Spain. Issue 4 (2nd October 2019) - Sande, J.; Peña, E.; Maciñeira, E.; Figuero, A.
ABSTRACT: The structural design of a breakwater is usually carried out by applying the verification equations existing in the literature in order to analyze the different failure modes. It is also common to perform complementary physical model tests for testing and optimization. The design of the Western Breakwater of Punta Langosteira, A Coruña, Spain was developed in accordance with the Level III probabilistic procedure defined in the Recommendations for Maritime Works (ROM) developed by the Spanish Port Authority. This paper presents the tests which were performed for the optimization of the design, the verification of the different failure modes and the verification equations used, and the determination of the stability reserve. In addition, the results have made it possible to verify the goodness of fit of the calculations, analyze the overall stability of the breakwater, and ultimately, optimize the final design.